Harmonizing Ethnomathematics-Based Green Behavior Integrated With Nangun Sat Kerthi Loka Bali Values in Education - Komang Srie Darmayanti; I Komang Agus Tri Antara; Gusti Ayu Komang Diva Triani; Kadek Yuni Dwi Setiani; Ni Kadek Yulanda Kusuma Wardhani; I Putu Pasek Suryawan; Ni Nyoman Parwati; I Made Ardana; Gusti Ayu Mahayukti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
The growing environmental degradation underscores the role of education in fostering green behavior among students. This study aims to explore the relationships among Nangun Sat Kerthi Loka Bali, green behavior, and Ethnomathematics, and to identify the role of Ethnomathematics in strengthening the development of green behavior in educational settings. This research employed a qualitative, phenomenological approach in four Adiwiyata Mandiri schools in Singaraja, Bali: SD N 1 Banyuning, SMP N 2 Singaraja, SMP N 6 Singaraja, and SMP N 3 Seririt, selected through purposive sampling. The study involved 12 informants, including representatives from the Department of Education, the Environmental Agency, and the Cultural Agency, as well as teachers and students. Data were collected through a literature review, in-depth interviews, and observations, and were analyzed using descriptive qualitative content analysis through the stages of data reduction, categorization, interpretation, and source triangulation. The findings reveal an integrative relationship among Sad Kerthi values, the six dimensions of green behavior, and Ethnomathematical activities embedded in school environmental practices. Ethnomathematics helps integrate environmental activities with mathematical concepts, thereby strengthening the development of meaningful green behavior. These findings indicate that integrating local wisdom values and Ethnomathematics can reinforce sustainable character education in schools.